(untitled) (Italian Journal of Public Health, 2012)
BACKGROUND: This study in the prospect of promoting adherence to the primary and secondary preven- tion programmes will research knowledge, attitudes and behaviors of the student population attending high schools regarding HPV infections and will also promote health education sessions based on peer education. METHODS: We carried out a community randomized trial regarding HPV infection, HPV vaccination, and sexual health, of students and a peer educational intervention. To verify the effectiveness of peer educators in changing opinions and beliefs about HPV a self-com- pletion questionnaire was made and distributed pre (T1) and post (T2) peer educator intervention. The same questionnaires were assigned to the control group. RESULT: The sample consisted of 900 students, mean age was 16.6±1.4, having relationship 34.4%. At T1, 64.6% of students in experimental group said that they knew HPV, 83.4% how it is transmitted and 71.1% HPV vaccination, 54.7% perceived dangerousness with significant gender-related difference. At T2 the percentages increased. At T1, 14.1% of females were vaccinated at T2 they were 17.5%. The main factors associated with the students’ propensity to vaccination were: having at least one sister; being in favour of vaccinations in general; knowing that the vaccine is aimed at preventing cervical cancer; and being aware that they could be infected by HPV. CONCLUSION: Both the HPV test and HPV vaccine need effective communication and monitoring of the spread of knowledge, especially among women identified as most in need of information and included in the age group at risk, in wich it is crucial to encourage informed choices. This underlines the need to plan adequate educational programmes.